A critical evaluation of the junior secondery school mathematics curriculam of the ministry of education of Sri Lanka - Ruberu, J. (My University, 1980)
The mathematics curriculum of the junior secondary school of this country has undergone profound changes during the past two decades. Revision of school mmathematics curriculem on a lardge scale commenced in the year 1964, beginning at the junior secondery level. The first phase of this revision was the development of a new ''intergareted'' mathematics curriculum....